2018
DOI: 10.1186/s40659-018-0184-5
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine deficiency contributes to synapse and neural circuit defects

Abstract: BackgroundThe previous studies have demonstrated the reduction of thiamine diphosphate is specific to Alzheimer’s disease (AD) and causal factor of brain glucose hypometabolism, which is considered as a neurodegenerative index of AD and closely correlates with the degree of cognitive impairment. The reduction of thiamine diphosphate may contribute to the dysfunction of synapses and neural circuits, finally leading to cognitive decline.ResultsTo demonstrate this hypothesis, we established abnormalities in the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Furthermore, the activities of transketolase and their common coenzymes thiamine diphosphate, GSH peroxidase, glutathione-S-transferase, and δ-aminolevulinate dehydratase (δ-ALA-D) have all been demonstrated to be decreased in AD (Sheu et al, 1988;Mastrogiacomo et al, 1996;Ansari and Scheff, 2010;Yu et al, 2018). Multiple metabolites altered by ApoE are identified within the PPP, including gluconolactone, gluconate, and G6P (Johnson et al, 2017).…”
Section: Altered Ppp In Aging and Admentioning
confidence: 99%
“…Furthermore, the activities of transketolase and their common coenzymes thiamine diphosphate, GSH peroxidase, glutathione-S-transferase, and δ-aminolevulinate dehydratase (δ-ALA-D) have all been demonstrated to be decreased in AD (Sheu et al, 1988;Mastrogiacomo et al, 1996;Ansari and Scheff, 2010;Yu et al, 2018). Multiple metabolites altered by ApoE are identified within the PPP, including gluconolactone, gluconate, and G6P (Johnson et al, 2017).…”
Section: Altered Ppp In Aging and Admentioning
confidence: 99%
“…Thiamine deficiency (TD) causes besides the weight loss, also disorders of nervous system and cardiomyopathy (Hoffman., ; Krasicka, Gralak, Sieranska, & Kulasek, ). It may decrease the membrane conductance, cause disorders in ATP production (Oliveira, Galan, Ribeiro, & Santos Cruz, ), brain failures (Aikawa et al, ; Ke, DeGiorgio, Volpe, & Gibson, ; Yu et al, ) and liver disorders (Hernandez‐Vazquez et al, ). Moreover, the TD may result in an increase of the frequency of death of cardiac cells (Zangen & Shainberg, ).…”
Section: Introductionmentioning
confidence: 99%
“…The thiamine deficiency was observed in Alzheimer’s disease and contribute to synapse and neural circuit defects. 45 …”
Section: Resultsmentioning
confidence: 99%
“…The thiamine deficiency was observed in Alzheimer's disease and contribute to synapse and neural circuit defects. 45 Previous studies have demonstrated that ASD genetic risk can act in part through expression quantitative trait loci, 46 namely, eQTL, and epigenetic regulation, 47 such as meQTL. Accordingly, we explored the association between microbes and the eQTL or meQTL SNVs.…”
Section: Snvs Correlated With Bacteria Taxamentioning
confidence: 99%